CORRELATION OF ENGLISH SCIENTIFIC VOCABULARY MASTERY WITH ENGLISH FOR SPECIFIC PURPOSES TEXT COMPREHENSION ON HEALTH SCIENCE SCHOOL STUDENTS - Atur Semartini; Lilik Ariyanti; Aulia Nur Rahmawati (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2023)
The purpose of this study was to investigate the correlation between mastery of English scientific vocabulary and comprehension of English for Specific Purposes (ESP) texts, particularly Microbiology and Physiotherapy texts. Data were obtained from 2 study programs: 16 Physiotherapy students and 26 Pharmacy students. Data were obtained by giving vocabulary and reading tests to students who had previously been taught English scientific vocabulary and reading of ESP texts. Vocabulary and reading materials taught and tested in the two Study Programs were different, based on the needs of the Study Programs. Data analysis was carried out using t test to determine the correlation between mastery of English scientific vocabulary and comprehension of ESP texts. Based on the analysis in Pharmacy students, there is a significant correlation between vocabulary scores and reading scores (P value <0.05). Meanwhile, in the correlation analysis of English scientific vocabulary mastery and physiotherapy texts comprehension, a value of 002 <0.05 was obtained, which means that there is a significant correlation of vocabulary scores and reading scores. Based on the results obtained, it can be concluded that there is a significant correlation between the mastery ​​of English scientific vocabulary and the comprehension of English for Specific Purposes Text.